Metode penyeduhan terhadap nilai kesukaan dan aktivitas antioksidan seduhan teh meniran (Phyllanthus niruri Linn.) - Ai Sri Kosnayani; Andi Eka Yunianto; Muhammad Eka Asri Rizal (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Meniran is an herbal plant that has many health benefits. Meniran tea contains phytochemicals like teas in general such as saponins, phenolics, flavonoids, and tannins. This study aims to determine the effect of the meniran leaf tea brewing method on the preference value and content of an antioxidant activity. This research was a laboratory experiment with a completely randomized design (CRD). Meniran tea was brewed using the Decoction Brew (DB), Cold Brew (CB), and True Brew (TB) methods with filter and non-filter treatments. The organoleptic test in this study used 30 untrained panelists. Organoleptic test data collection consisting of color, aroma, and taste attributes were assessed using a 9-scale hedonic scale questionnaire. Organoleptic data that had been collected was then tested for normality using Kolmogorov Smirnov, if normally distributed, continued with ANOVA statistical test and then Duncan's further test with 99% CI. Organoleptic test results in the form of attributes of color (p= 0,000), aroma (p= 0,003), and taste (p= 0,000) of panelists preferred tea with the TBF brewing method. Based on the antioxidant activity content of selected meniran tea (TBF) around 2,33 – 2,81 mg/mL. In conclusion, the panelists prefer tea with the TBF brewing method based on the attributes of color, aroma, and taste as well as high antioxidant activity.